2014
DOI: 10.7860/jcdr/2014/9967.4684
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge, Attitudes and Practices Survey regarding Sex, Contraception and Sexually Transmitted Diseases among Commerce College Students in Mumbai

Abstract: Participants, especially females, lacked basic information about sexuality and related concepts. Male participants had a very casual attitude towards having sex with multiple partners. Premarital sex is more common than once believed. In the light of our finds and the current scenario, sexuality education is indispensable in order to guide the youth to develop and adopt healthy and appropriate sexual practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…In addition, the lower Traditional sexual morality found in our male students was consistent with Higgins, et al [9], a research showing that men reported lower sexual morality and had more liberal attitudes to the premarital sex and homosexuality. The higher Sexual knowledge in our male students was consistent with the finding that women had less knowledge about sex than men [26,27]. Furthermore, people with less accurate sexual knowledge were more likely to have conservative sexual attitudes [28].…”
Section: Statistical Analysessupporting
confidence: 87%
“…In addition, the lower Traditional sexual morality found in our male students was consistent with Higgins, et al [9], a research showing that men reported lower sexual morality and had more liberal attitudes to the premarital sex and homosexuality. The higher Sexual knowledge in our male students was consistent with the finding that women had less knowledge about sex than men [26,27]. Furthermore, people with less accurate sexual knowledge were more likely to have conservative sexual attitudes [28].…”
Section: Statistical Analysessupporting
confidence: 87%
“…The knowledge of sex as well as sexual activity was significantly higher as the age or education level increases. Although the prevalence of sexual activity was comparable to other Indian studies [ 5 6 ] but the prevalence of sexual intercourse is much higher in our study. Ramadugu et al .…”
Section: Discussionsupporting
confidence: 75%
“…Premarital sex was reported by 48% boys and 18% girls. [ 5 ] In another study by Sscbunya et al . in 2019 in Uganda, the prevalence of sexual activity was 67.6% among females.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may be attributed to the cultural context of the study population. 8,32 The attitude of medical students is important, because it can lead to social stigma, exclusion, denial, avoidance of care, negligence and distancing from people with HIV/AIDS, which may in turn lead to discrimination in service delivery, poor quality of patient care, and increased treatment costs for these patients. Medical students receive sufficient training and face different cases of this disease throughout their studies, which may provide an opportunity to project a positive attitude toward all patients regardless of the nature of their infection.…”
Section: Discussionmentioning
confidence: 99%